One Health Approach to Study the Occurrence and Antimicrobial Resistance of Extended-Spectrum β-Lactamase- and Carbapenemase-Producing Escherichia coli and Klebsiella spp. in Urban Agriculture in Burkina Faso - Fatimata Bintou Josiane Diarra; Isidore Juste Ouindgueta Bonkoungou; Zakaria Garba; Namwin Siourimè Somda; Djifahamaï Soma; Marguerite Edith Malatala Nikiema; Evariste Bako; Souleymane Sore; Natéwindé Sawadogo; Nicolas Barro; Kaisa Haukka (Microorganisms)
Data on antimicrobial resistance in Burkina Faso’s agricultural sector is still limited. This study assessed the occurrence of extended-spectrum β-lactamase-producing Escherichia coli (ESBL-Ec) and Klebsiella spp. (ESBL-K) in lettuce, environment, and gardeners’ stools in market gardens in Ouagadougou, Burkina Faso. A total of 356 samples were collected from three vegetable gardens (76 lettuce, 76 soil, 62 manure, 63 irrigation water, and 79 human stools). The ESBL-selective medium was used for initial selection of ESBL-producing bacteria, and the isolates were further identified using biochemical tests. An antibiotic susceptibility test was performed using the disk diffusion method. The overall prevalence of ESBL-Ec and/or ESBL-K in the samples was 232/356 (65.2%). Of the lettuce samples, the prevalence of ESBL-Ec was 19/76 (25.0%) and ESBL-K 33/76 (43.4%). In the market gardens environment, the prevalence of ESBL-Ec was 32/201 (15.9%) and ESBL-K 124/201 (61.7%). In the gardeners’ stools, the prevalence of ESBL-Ec was 42/79 (53.2%) and ESBL-K 24/79 (30.4%). Two ESBL-K isolates were found to produce NDM carbapenemase. Due to the high prevalence of ESBL-producing bacteria, which may also be carbapenemase producers, it is necessary to monitor pathogens in agricultural products with a “One Health” approach to limit and prevent infections in the population.